Best Answer

Assuming you mean x squared plus 5x squared... the answer is 6x squared.

Q: What is x2 plus 5x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

5x2+500 = 844.45 5x2 = 844.45-500 5x2 = 344.45 x2 = 344.45/5 x2 = 68.89 x = the square root of 68.89 = 8.3 x = 8.3

9. And the word is minus, not minis.

5x2 - 136 = 44 5x2 - 136 + 136 = 44 + 136 5x2 = 180 5x2/5 = 180/5 x2 = 36 âˆšx2 = âˆš36 x = Â±6

To factor any term, divide by the LCF (largest common factor) of the term. For 5x2-45, the LCF is 5. 5x2-45 = 5(x2-9) It can, of course, be factored even further to become: 5(x2-9) = 45(x2/9 - 1) but when factoring, we usually don't need to go past 5(x2-9) (for example, you've figured out that x2 = 9, thus x = +/- 3.)

= 5x2+70-16+9x-2 = 5x2+9x+52 = 5x2+9x1+52 This implies coefficient of degree 1 is 9. Ans.

Related questions

5x2 - 20xy + 10y2 = 5(x2 - 4xy + 2y2) which cannot be simplified into rational factors.

5x2+500 = 844.45 5x2 = 844.45-500 5x2 = 344.45 x2 = 344.45/5 x2 = 68.89 x = the square root of 68.89 = 8.3 x = 8.3

5x2 + 20 = 5*(x2 + 4) which cannot be factorised further.

i thinking this answer should be -20

(3x - 5x) + (x2 - 6x2) = -2x -5x2 = -x(2 + 5x)

If that's 5x2, it factors to (x + 5)(x2 + 1)

5x2 + 25x + 30 This expression describes a parabola, and can be factored out as follows: = 5(x2 + 5x + 6) = 5(x + 2)(x + 3)

4x2 + 1 + x2 + 3 = 5x2 + 4

(3x + 5)(x2 - 2)

If you mean: f(x) = x4 - 3x3 + 5x2 / x2 then: f(x) = x4 - 3x3 + 5 ∴ f'(x) = 4x3 - 9x2 If you mean: f(x) = (x4 - 3x3 + 5x2) / x2 then: f(x) = x2 - 3x + 5 ∴ f'(x) = 2x - 3

x3 + 5x2 - x - 5 = (x2 - 1)(x + 5) = (x + 1)(x - 1)(x + 5)

9. And the word is minus, not minis.